Chemical looping at the nanoscale — challenges and opportunities. (June 2018) - Mishra, Amit; Li, Fanxing
Abstract : The activity and long-term performance of oxygen carrier particles, which undergo cyclic reduction–oxidation (redox) reactions at elevated temperatures, are of critical importance to chemical looping processes. Although the significant thermal and redox stresses in chemical looping reaction make it challenging to stabilize metal oxide based oxygen carriers at the nanoscale, a number of promising approaches have been proposed and investigated over the past decade. This article summarizes recent advances in nanoscale oxygen carrier development. Mechanistic insights in the redox reactions of the oxygen carriers and their implications for the design and optimization of oxygen carriers for chemical looping combustion and partial oxidation reactions are also discussed.